Expectations and experiences of women presenting to emergency departments with early pregnancy bleeding. (1st December 2019) - See, Stephanie YC; Blecher, Gabriel E; Craig, Simon S; Egerton‐Warburton, Diana
Abstract: Objective: To explore women's expectations and experiences when presenting to the ED with early pregnancy bleeding. Methods: We conducted a qualitative study where women presenting to the ED with early pregnancy bleeding participated in two semi‐structured interviews. An initial interview explored expectations of care and was conducted prior to ED treatment. A follow‐up interview about experiences with care was conducted after discharge from the ED. Women were recruited from three EDs in suburban Melbourne: one tertiary referral centre and two urban district hospitals. Results: Thirty women with early pregnancy bleeding completed the initial interview and 22 completed the follow‐up interview. Eleven participants were primigravid women and 21 participants had never experienced early pregnancy bleeding prior to their ED presentation. Four themes relating to the patient experience were identified: (i) Acknowledgement of patients' concerns by hospital staff, including informing patients of progress and explanation of investigation results; (ii) Early pregnancy bleeding as a distressing experience, with most participants expecting that this would be acknowledged by ED staff, and privacy provided to allow for grieving; (iii) Prolonged waiting time for an urgent medical condition; and (iv) Ongoing care and support, such as providing recommendations of available services to support patients on discharge from the ED. Conclusion: Early pregnancy bleeding is a distressing and anxiety‐provoking experience for women attending the ED. Appropriate emotional support is critical to the holistic care for those seeking emergency care.